Penerapan Asas Itikad Baik dalam Pembuatan Perjanjian Waralaba sebagai Dasar Pembuatan Kontrak - Muhammad Masudi; Budi Santoso (Syntax Literate, 2023)
Standard agreement is a contract that tends to be one-sided and violates the principle of good faith. It is different from what is stated in Article 1338 (3) of the Civil Code that the Agreement must be executed in good faith. In practice, the application as the basis for the formation of franchise agreements, the cause of deviations in rights and obligations by strong parties, resulting in the loss of weak parties. so that it looks far from the values of justice. To find out whether the principles are applied in making a franchise agreement is to pay close attention to the provisions/articles governing the rights and obligations of the parties. This study aims to determine the application of the principle as the basis for making franchise agreements and the legal consequences if the principle is not carried out. Empirical juridical research methods, with the specifics are descriptive analytical. the conclusion of the application of that in the franchise agreement must be treated for the fulfillment of the rights and obligations of the parties, the legal effect on the principle is that the agreement is null and void or voidable.